ANALISIS PREFERENSI KONSUMEN TERHADAP ATRIBUT SAYURAN SEMEN/CECIWIS ALIAS DAUN DARI TUNAS BUNGA KOL YANG SUDAH DIPANEN (Analysis of Consumer Preferences Towards The Attributes of Semen/Ceciwis Vegetables aka Leaves From Harvested Cauliflower Stuffs) - Dewi Anggun Oktaviani; Novita Lidyana; Yennyka Leilasariyanti (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabay, 2024)
This study aims to analyze consumer preferences for cement/ceciwis vegetables, see the most preferred attributes of cement/ceciwis vegetables and the most dominant attributes to be developed in cement/ceciwis vegetables. The method used in this study is the descriptive survey method. The sample withdrawal method in this study is by using the Accidental Sampling method of 50 respondents with primary data from interviews using a questionnaire tool. The data were analyzed using the konjoin analysis method with SPSS 25. The results of this study show that the consumer utility value for semen/ceciwis vegetables in a clean condition is (0.255), has an even freshness level of (0.195), price <= Rp. 8,000 is (0.195), durability > from 5 days is (0.025), and easy to obtain is (0.075). Importance Score) used as a consideration material for respondents/consumers of Semen/Ceciwis vegetables in order from the highest to the lowest are Cleanliness Level of 26,613, Price and Freshness of 21,496, Durability of 17,342 and Availability of 13,513 The cleanliness level of Semen/Ceciwis Vegetables is one of the attributes that is highly considered by consumers in making a purchase decision, this can be seen from the usability value of 0.255 and the importance of by 26,613 which is higher than other attributes. The marketing strategy that can be used to increase the sales of semen/ceciwis vegetables is to use a marketing strategy, namely the marketing mix or often called the 4P because it consists of a mix of products, prices (price), places (place), and finally a promotion mix (promotion). Keywords: Conjoint Analysis, Preferences, Semen/Ceciwis Vegetables.